2012
DOI: 10.1089/cyber.2011.0511
|View full text |Cite
|
Sign up to set email alerts
|

The Real You? The Role of Visual Cues and Comment Congruence in Perceptions of Social Attractiveness from Facebook Profiles

Abstract: The purpose of this study was to examine the effects of social cues in self-presentations and the congruence of other-generated comments with the self-presentation in people's evaluations of a profile owner. A 2 (level of social cues: high vs. low) × 2 (congruent vs. incongruent) × 2 (order) × 2 (multiple messages) mixed-subject experiment was conducted with 104 college students. The results showed that a profile owner was perceived less socially attractive when other-generated comments were incongruent with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 28 publications
2
39
1
2
Order By: Relevance
“…In addition, group photos and group selfies were not perceived as more socially attractive. These results contradict previous findings that the number of social cues in profile photos on Facebook is positively correlated with the perceived social attractiveness (Milyavskaya et al, 2010; Hong et al, 2012). One possible explanation for our finding might be that we asked the participants to concentrate on the evaluation of the profile owner.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, group photos and group selfies were not perceived as more socially attractive. These results contradict previous findings that the number of social cues in profile photos on Facebook is positively correlated with the perceived social attractiveness (Milyavskaya et al, 2010; Hong et al, 2012). One possible explanation for our finding might be that we asked the participants to concentrate on the evaluation of the profile owner.…”
Section: Discussioncontrasting
confidence: 99%
“…This phenomenon is also called the attractiveness halo effect (Kaplan, 1978). Besides this effect, there might also be a more direct route of attributing social attractiveness on Facebook: Hong et al (2012) found evidence that a higher number of social cues in Facebook profile pictures is positively related to social attractiveness and popularity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Utz (2010) found that friends' postings significantly affected observers' ratings of the profile owner's honesty, reliability, and social attractiveness. In another study, profile owners were perceived as less socially attractive when friends' postings were incongruent with the profile owner's self-postings, suggesting that, no matter what type of self-image Facebook users attempt to convey, they will not be successful without validation from others (Hong, Tandoc, Kim, Kim, & Wise, 2012).…”
Section: Impact Of Risky Sns Practices On Cyberbullying Victimizationmentioning
confidence: 99%
“…Several related studies have demonstrated how information posted online by third parties can influence perceptions of a social network site user. Specifically, comments by friends on social network sites have been demonstrated to affect perceptions of a user's popularity (Hong, Tandoc, Kim, Kim, & Wise, ), physical attractiveness (Walther et al, ), and social attractiveness (Antheunis & Schouten, ). Although many studies have demonstrated that, on social network sites, contributions made by third parties affect impressions of a profile owner, it is difficult to locate any studies that (a) directly measure perceptions of warranting value, (b) establish that third‐party claims are perceived to have greater warranting value than self‐claims, and (c) demonstrate how perceptions of warranting value moderate the effect information has on impressions.…”
Section: The Source Of Information As a Warranting Cuementioning
confidence: 99%